Mental Readiness Of Banjarbaru Male Volleyball Athletes In Facing The 2025 Provincial Championship - Nur Fitriani, Ika; Anggara, S.Pd., M.Pd , Norma; Perdinanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to examine the mental readiness of Banjarbaru male volleyball athletes in facing the 2025 South Kalimantan Provincial Championship (Kejurprov). Mental readiness is an important factor because it can affect athlete performance during the match, especially in stressful situations that require high concentration. A strong mentality will help athletes to stay focused, confident, and able to control their emotions when facing tough opponents. This study uses a quantitative descriptive method involving 12 athletes as respondents. Data collection was carried out through a questionnaire that had been validated by experts in the field of sports psychology. The results showed that the level of self- confidence of the athletes was in the fairly good category, with an average of 60.75%, while their anxiety level was relatively low, with an average score of 19.17%. This shows that in general the athletes have good mental readiness to face the match. This study is expected to be a reference for coaches and support teams to improve their mentality so that the athletes' performance during the match is more optimal.